Status of the Modern General Theory of the State and Law in the System of the Legal Sciences - Vladimir Valentinovich Kozhevnikov (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This scientific article deals with the problem of the hierarchy of the modern legal sciences. The main purpose of the work is to justify the principle that modern general theory of the state retains the status of the fundamental, methodological legal science. There are following tasks of the achieving of the purpose in the article: 1) to analyse the positions of the legal scientists who doubt on the high status of the general theory of the state and the law; 2) to characterize Marxist-Leninist general theory of state and law, which had class, party character; 3) to justify the position that certain provisions of Marxism-Leninism have not lost relevance yet; 4) to display the similarity of Marxist-Leninist general theory of the state and law and modern theory of state and law in terms of methodological foundations. Result. Not agreeing that the theory of the state and law has the function of the serving of the official ideology currently, there is a suggestion in the article that the general theory of the state and law at all stages of the development of the society, not excluding the modern science, is the fundamental, methodological science in the system of other legal sciences, despite the attacks at both theoretical and practical levels.